Copy number variations in testicular maturation arrest. (19th February 2017) - Halder, A.; Kumar, P.; Jain, M.; Iyer, V. K.
Summary: Testicular maturation arrest is characterized by interruption of germ cell development and differentiation. Genetic factors play important role in the causation of human disease, including male infertility. The objective was to study copy number variations in testicular maturation arrest using single nucleotide polymorphism (SNP) microarray technique. Conventional cytogenetics, targeted fluorescence in situ hybridization (FISH) and sequence‐tagged site (STS) polymerase chain reaction (PCR) were used to confirm some of the SNP microarray findings. SNP microarray on 68 cases of testicular maturation arrest detected copy number variations (CNVs) mostly on sex chromosomes involving pseudoautosomal regions (PAR) 1, 2 and 3 as well as azoospermic factors (AZFs) besides three cases of chromosomal abnormalities (two Klinefelter syndromes and one case of dicentric Y). The AZF deletion was observed in 14 (20.6%) cases and the AZFc gain was observed in 6 (8.8%) cases. PAR 1 and 2 CNVs was observed in 5 (7.3%) cases. PAR 3 CNVs was detected in 19 cases and 2 controls. The TSPY2 gene gain (within PAR 3 CNVs) was observed in 16 cases and 1 control. CNV containing autosomal genes possibly associated with male infertility in this study was SPATA31A2‐A5 (9p12) in five cases. In this study, SNP microarray identified possible underlying aetiology in 55.9% (38/68) cases besides identifying minimal critical region of AZFc deletion as 0.51 mb (Y:24356128–24873665) involving TTY5, RBMY2FP, RBMY1F, RBMY1J, TTY6 and PRY genes. SNP microarray seems superior, sensitive, specific as well as cost‐effective method and has potential to be the first tier investigations to explore underlying genomic factors of testicular maturation arrest. The present study is an attempt to find out probable genomic factors with idiopathic testicular maturation arrest.